Análise dos condicionantes ambientais na formação de voçorocas no município de Capão do Cipó - RS - Gaberti, Marinéli Moraes (2022)
Over time, erosion has caused considerable damage to society through the loss of fertile soil and the silting up of waterways. The importance of this work is due to the identification of several deep linear erosion processes in the municipality of Capão do Cipó/RS, even though it is located on the Serra Geral plateau. In this context, the understanding of the natural/anthropic genesis and the occupation of spaces, sometimes inadequately and causing serious consequences to the environment, imposes the need for environmental studies. Thus, the general objective of this work is to identify and analyze the environmental conditions more prone to the formation of gullies in the municipality of Capão do Cipós-RS. To understand the problem, a survey of the characteristics of the relief, lithology, soils and land use and occupation was carried out. In this research a systemic approach was used aiming at the study of erosion, in view of its broad history of use for environmental analysis, with the support of geoprocessing tools. This work allowed us to identify 33 gullies, to analyze the main forms of the gullies, their relationship with the drainage network, and attributes of the relief, making it possible to understand the controlling factors of the development of the processes, and to support planning and management proposals.